(untitled) (Società e diritti, 2016)
The existence of the society implicates that a human wish, expression of the collectivity, rules the relationships among the men that make part of it: the right defines contrasts her juridical spheres of the partners through a delimitation of the whole reality. In how much it has normative nature, the right constitutes a formal datum, that can be contrasted to that substantial of the society, on which comes to engrave. The juridical form is the conceptual representation of the reality, it is the idea that represents the things on their mutual relationships. Juridical reality is more properly nevertheless reserved to that formal aspects that are expression of categorical juridical norms and not hypothetical, and therefore in degree to create a structure. As human work, the right is not identified with the moral norms, even if its finalities, of guarantee of the existence of a social body, they are ethically valid.